2006
DOI: 10.1097/01.ico.0000240086.56522.69
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Epithelial Ingrowth After LASIK Enhancement With a Combined Technique of Mechanical Debridement, Flap Suturing, and Fibrin Glue Application

Abstract: Severe progressive epithelial ingrowth may be treated successfully with a combination of mechanical debridement, flap suturing, and fibrin glue application.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 14 publications
(16 reference statements)
0
18
0
1
Order By: Relevance
“…Treatment includes mechanical debridement and flap reattachment. Successful cases of flap attachment has been reported with no recurrence of epithelial ingrowth or fluid accumulation in the interface [107][108][109][110]. Azar et al treated recurrent epithelial ingrowth after LASIK by attaching an annular AM graft with fibrin glue [111].…”
Section: Epithelial Ingrowth and Other Laser-assisted In Situ Keratomilmentioning
confidence: 99%
“…Treatment includes mechanical debridement and flap reattachment. Successful cases of flap attachment has been reported with no recurrence of epithelial ingrowth or fluid accumulation in the interface [107][108][109][110]. Azar et al treated recurrent epithelial ingrowth after LASIK by attaching an annular AM graft with fibrin glue [111].…”
Section: Epithelial Ingrowth and Other Laser-assisted In Situ Keratomilmentioning
confidence: 99%
“…[18][19][20] Fibrin glue has also been successfully used to secure AM in cases with corneal ulcers or perforations, 21,22 scleral melt, 23 conjunctivochalasis, 24,25 and pterygium. 26 It has been shown that in contrast to suturing, epithelial growth takes place only over AM when fibrin glue is used for central epithelial defects in rabbit corneas.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…One problem with this technique is the induction of astigmatism (Narvaez et al, 2006). An alternative method of scraping and suturing with the application of fibrin glue has been found to reduce the induction of astigmatism (Narvaez et al, 2006).…”
Section: Epithelial Ingrowthmentioning
confidence: 99%
“…One problem with this technique is the induction of astigmatism (Narvaez et al, 2006). An alternative method of scraping and suturing with the application of fibrin glue has been found to reduce the induction of astigmatism (Narvaez et al, 2006). Ethanol and mitomycin treatments have also been proposed as methods to destroy epithelial ingrowth but are not as reliable due to their toxic effects (Wang and Maloney, 2000).…”
Section: Epithelial Ingrowthmentioning
confidence: 99%